2012
DOI: 10.1080/00087114.2012.760882
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic characterization of three allopatric species of Hypostomus Lacépède (1803) (Teleostei, Loricariidae)

Abstract: The genus Hypostomus is distributed throughout South America and is one of the most widely studied genera among Loricariidae, with approximately 130 species described. However, correct taxonomic identification is difficult due to subtle morphological differences between species. Thus, cytogenetic data on this genus are fundamental to clarifying the evolutional history of the group. Cytogenetic analyses were carried out on three species of Hypostomus in the state of Paraná, Brazil: one from the Tibagi river bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The chromosomal data in this study showed that 2n = 68 and different karyotype formulae between H. commersoni and H. derbyi could be explained by pericentric inversions. Cytogenetic analysis in H. derbyi from the Iguaçu river in Curitiba, Paraná state, showed a different karyotype formula 51 and can suggest chromosomal diversification and cryptic species for H. derbyi. In Hypostomus, the number of st/a chromosomes was postulated to be directly proportional to an increase in 2n 13 .…”
Section: Discussionmentioning
confidence: 98%
“…The chromosomal data in this study showed that 2n = 68 and different karyotype formulae between H. commersoni and H. derbyi could be explained by pericentric inversions. Cytogenetic analysis in H. derbyi from the Iguaçu river in Curitiba, Paraná state, showed a different karyotype formula 51 and can suggest chromosomal diversification and cryptic species for H. derbyi. In Hypostomus, the number of st/a chromosomes was postulated to be directly proportional to an increase in 2n 13 .…”
Section: Discussionmentioning
confidence: 98%
“…The maintenance of the diploid number in the plecos in this study, for example, seems to be a group tendency, since the great majority of the studied populations present 2n = 68 chromosomes (Artoni and Bertollo 1996;Alves et al 2006;Bueno et al 2012;Rubert et al 2011;Endo et al 2012;Alves et al 2012;Fernandes et al 2012;Pansonato-Alves et al 2013;Traldi et al 2013;Lara-Kamei et al 2017) and this could represent an adaptive and ancestral state. The exception for this character is an isolated population in the Tibagi River (Maurutto et al 2012) and a case of a new species of the H. ancistroides complex carrying a differentiated sexual chromosomal system, which is very divergent from the others (Rocha-Reis et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although variable when observing the totality of the karyotype macrostructure, the presence of C-banding in some chromosomes of all karyomorphs may indicate the existence of some homology (Rubert et al 2011;Fernandes et al 2012;Maurutto et al 2012;Pansonato-Alves et al 2013;Traldi et al 2013;Lara-Kamei et al 2017;Rocha-Reis et al 2018), and may even be considered a phylogenetic sign. In this study, we observed the presence of conserved C+ blocks in pairs of chromosomes 4 (m), 7 (sm) and 26 (a), in a pericentromeric or subterminal region (Figures 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All previously de- [Maurutto et al, 2012] and the one investigated here ( Fig. 1 A, B), which have 2n = 66.…”
Section: Discussionmentioning
confidence: 99%